IDENTIFIKASI TENTANG PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 2 LAMONGAN - THORIDA NUR ASIH (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
The role of teaching material in the learning process among other things help teachers deliver the material, being the main reference, a good selection of learning materials is a rigorous selection process so that the proper materials are used. Because not all teaching material that is worth used. So this research aims to find out what types of materials are used, along with the reason as well as to determine the feasibility of teaching material of economic subjects accounting material used in SMA Negeri 2 Lamongan based on criteria that includes four components BSNP feasibility feasibility component, is the content preparation, language and graph. The results of the research note that the teaching material used in SMA Negeri 2 Lamongan is a textbook and LKS, textbook selected by reason of partnership between publishers with the school while LKS were selected to complement the existing deficiencies in the textbook, as well as component results can be seen after the eligibility and it is known all textbook got a percentage amounting to 91,45%, LKS 57,04%, which it does very decent textbook and LKS worthy. Keyword : Identification, teaching materials, materials accounting